2007
DOI: 10.1111/j.1523-536x.2006.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Maternal Death in Mexico

Abstract: Background: One of the United Nations' Millennium Development Goals for 2015 is to reduce the maternal mortality ratio by three fourths. Ninety-nine percent of maternal deaths occur in developing countries, and the World Health Organization encourages investigations in these settings to determine the risk factors of maternal deaths. Our aim was to identify these risk factors in a hospital-based study in Mexico. Methods: The study was conducted at the Hospital of Obstetrics and Gynecology at the Mexican Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
1
19
0
2
Order By: Relevance
“…We found only five articles presenting reference ranges for CPR. Table 1 describes the main characteristics and number of citations of the 19 selected studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…We found only five articles presenting reference ranges for CPR. Table 1 describes the main characteristics and number of citations of the 19 selected studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] .…”
Section: Resultsmentioning
confidence: 99%
“…Insert Table 1 Of the seven studies identified, all were observational studies. Most of the studies (6) were retrospective 17,[22][23][24][25][26] , and one was prospective 20 . Of the 6 retrospective studies 17,[22][23][24][25][26] , 3 were case-control 22,24,26 and 3 cross-sectional 17,23,25 .…”
Section: Resultsmentioning
confidence: 99%
“…Four articles calculated mortality rates according to mode of delivery [5,11,13,17]. Cesarean sections included both elective and emergency deliveries, and vaginal deliveries composed of both spontaneous and operative deliveries.…”
Section: Resultsmentioning
confidence: 99%
“…Indirect causes may depend on a suboptimal general health status of women in the reproductive period. RomeroGutierrez et al [13] showed by a regression model that maternal age, marital status, number of antenatal visits, previous obstetrics complications and preexisting medical conditions are significantly associated with maternal mortality. Therefore, a detailed investigation of risk factors before conception may be useful to identify, since the early stages of pregnancy, women at elevated risk of death.…”
Section: Discussionmentioning
confidence: 99%